INTELLIGENT DATA ANALYSIS AND CLOUD COMPUTING - M. M. Tatur; M. M. Lukashevich; D. Y. Pertsev; N. A. Iskra (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
In this paper the term of «intelligent data analysis» is discussed, the cloud computing concept is described. The system developed and deployed on the computer cluster by ECM department of BSUIR is shown as an example of the intelligent data analysis by means of cloud computing. Some results of research with the help of this system are given.